Holistic approaches to sustainable photovoltaic development in the Nordics - Ranta, Samuli (fi=Turun yliopisto|en=University of Turku|, 2025)
This thesis investigates key aspects of photovoltaic (PV) systems to enhance their sustainability and economic viability, particularly in high-latitude environments such as Finland. This work focuses on four main subjects: the use of sustainable materials, the reliability of new PV module designs under snow load, the development of advanced modelling tools, and the grid integration of PV systems. Surmounting the environmental and economic challenges facing PV systems is critical to enhancing their sustainability, which is addressed in this study. Although significant research findings have already facilitated the reduction of greenhouse gas (GHG) emissions directly attributable to PV modules, a substantial portion of total emissions attributable to PV systems are now accounted for by PV system substructures. A key finding of this research is the potential to achieve substantial reductions in total PV system GHG emissions by replacing steel with wood-based products. This material substitution not only reduces the PV system carbon footprint by 48% in the base-case scenario but is also shown to be 25% more cost-effective. Furthermore, this research investigates the reliability of modern, cost-effective PV modules, which often feature thin-glass technology. The research findings reveal that such designs make PV modules susceptible to localised fractures under heavy, non-uniform snow loads, a vulnerability that is not always detected by current standard tests. To address this issue, a novel acoustic analysis method is proposed for identifying these subtle design failures. In addition, advanced simulation tools for non-conventional PV configurations, such as vertical east-west bifacial PV systems and bifacial PV canopy systems, are developed and validated to optimise their performance under Nordic conditions. Ultimately, this dissertation demonstrates that vertical east-west bifacial PV systems are highly beneficial for grid stability and greatly enhance economic returns under Nordic conditions, as their morning and evening production peaks align well with electricity demand and pricing, thus increasing grid hosting capacity and overall value for prosumers.

Holistisia lähestymistapoja kestävään aurinkosähkön käyttöönottoon pohjolassa Tämä opinnäytetyö tarkastelee aurinkosähköjärjestelmien (PV) keskeisiä osa-alueita kestävän kehityksen ja taloudellisen kannattavuuden parantamiseksi, erityisesti pohjoisilla leveysasteilla, kuten Suomessa. Työ jakaantuu neljään pääteemaan: kestävien materiaalien käyttöön, uusien aurinkopaneelien luotettavuuteen lumikuorman alla, mallinnustyökalujen kehittämiseen ja aurinkosähköjärjestelmien sähköverkkointegraatioon. Tutkimuksessa osoitetaan, että aurinkosähköjärjestelmien kestävyyden parantaminen on ratkaisevan tärkeää. Merkittävää on, että vaikka paneelien hiilijalanjälkeä on jo onnistuttu pienentämään, suuri osa järjestelmän kokonaispäästöistä syntyy nykyisin niiden alusrakenteista. Tämän työn keskeinen löydös on, että korvaamalla teräs puupohjaisilla tuotteilla voidaan esimerkkitapauksessa saavuttaa merkittäviä päästövähennyksiä, järjestelmän hiilijalanjälki laski jopa 48 % ja se oli lisäksi 25 % kustannustehokkaampi. Lisäksi tutkimus keskittyy nykyaikaisten, kustannustehokkaiden ja usein ohutta lasia hyödyntävien aurinkopaneelien luotettavuuteen. Paljastui, että tällaiset rakenteet ovat alttiita paikallisille murtumille epätasaisen lumikuorman alla, mitä nykyiset standarditestit eivät aina havaitse. Tämän ongelman ratkaisemiseksi esitellään uudenlainen akustinen analyysimenetelmä, jolla nämä hienovaraiset vauriot voidaan tunnistaa. Työssä on myös kehitetty ja validoitu uudenlaisia simulaatiotyökaluja epätavanomaisille aurinkosähkökonfiguraatioille, kuten itä-länsi suunnatuille pystysuorille kaksipuolisille (VBPV) paneeleille ja PV-autokatosjärjestelmille. Tulokset osoittavat, että VBPV järjestelmät parantavat huomattavasti sähköverkkoon integroitavuutta ja tuottavat paremman taloudellisen tuoton pohjoisissa olosuhteissa. Tämä johtuu siitä, että niiden tuotantohuiput ajoittuvat aamuun ja iltaan, mikä vastaa paremmin sähkön kysyntää ja hintoja.